EFEKTIVITAS BERKUMUR LARUTAN DAUN BINAHONG TERHADAP INDEKS PLAK PADA SISWA KELAS III – IV ANAK SEKOLAH DASAR NEGERI 21 MANADO KOTA MANADO - Jeineke Ratuela; Anneke Tahulending (Poltekkes Kemenkes Medan, 2024)
Dental plaque is a soft deposit that adheres tightly to the surface of the teeth, consisting of icroorganisms that multiply in an intercellular matrix if a person neglects dental and oral hygiene. Anredera cordifolia (Ten) Steenis or commonly known as binahong or gondola is a creeping plant that is perennial (long-lived). The benefits of the binahong leaf plant are enormous in the world of medicine, empirically binahong can cure various types of diseases. In medicine, the part of the plant used can come from the leaves. Research using boiled leaves has found many ingredients, which were stated by (Setiaji, 2009) that flavonoids have various effects, namely analgesic, anti-inflammatory and as a vasolidator. The aim of this research was to determine the effectiveness of gargling binahong leaf solution on plaque index. This type of research is True Experiment research with a